Institutional Reforms for Getting an Agricultural Knowledge System to Play Its Role in Economic Growth (The Quaid-i-Azam Memorial Lecture) (The Pakistan Development Review, 1999)
While alarmists shriek the crisis of accelerating soil erosion and declining water quality as the major impediment to the future of global agriculture in supplying the needs of humanity, the argument here is that, although resource degradation is indeed a threat to achievement of satisfactory crop yields over the next several decades, the main threat is not degradation of natural resources. Rather, it is degradation of the capacity of societies, particularly those in the less-developed countries, to develop the knowledge embodied in people, technology and institutions necessary to meet the challenge of higher yields and intensified agricultural production. Dealing with this threat of degradation of knowledge institutions and resources must be an important focus of economic development policy in agrarian societies. In short, the agricultural knowledge and information systems (AKISs) serving the developing world must be put in effective and stable shape to deliver the needful.